Venturing Into Agrientrepreneurship: A Study On Enablers And Constraints - B. Shilpa; Tanya Saklani; B Gopichand; G Naveen Kumar; Mahantesh Shirur (Journal of Agricultural Extension Management, 2026)
Agriculture sector is critical to the growth and development of India as majority rely on agriculture. With the changing landscape of agriculture and the way it is shifting from subsistence to commercial farming, the role of private extension service providers is assuming greater significance. This trend is alluring the private individuals to engage into Agripreneurship activities. Even many involved in farming are showing interest to shift to Agripreneurship by diversifying their activities and income sources. Becoming the seller of agri-inputs and information to the farmers in varying scale is a new agribusiness opportunity for many in different regions of the country. The Diploma in Agricultural Extension Services for Input Dealers (DAESI) is a scheme of Agriculture Ministry of Government of India to train and enable the candidates aspiring to become agripreneurs to embracing agri-input business. However, venturing into such untraversed road without enablers is likely to cause disruptions to the livelihood of small agripreneurs. Such ventures are also likely to encounter several constraints for which necessary policy facilitation may be put in place. The present study identifies such enablers and constraints encountered by the candidates completing the DAESI program based on the data collected from 600 respondents in 10 different states of India. The study also suggests policy recommendations to give impetus to aspiring agripreneurs to take up Agripreneurship activities and support farming community in India.